Audit Firm Attributes And Independence Of Auditors: Evidence From Nigeria’s Listed Manufacturing Companies: Array - Sanni, Mubaraq; Abdulazeez, Taofeeq; Mudathir, Babatunde (The Journal of Accounting and Management, 2021)
Introduction: This study is carried out to ascertain how attributes specific to audit firms affect the independence of auditors engaged by manufacturing listed companies on the Nigerian Stock Exchange Market (NSE). Objective: This study sought to examine audit attributes and independence of auditors: evidence from listed manufacturing companies, Nigeria. Methodology: Research survey conducted on 26 listed manufacturing companies with head offices in Lagos, Nigeria. The companies were selected by using the Taro Yamani method while simple random sampling was used to select the respondents and total numbers of 78 questionnaires were administered. The data collected from the survey was analyzed with the aid of Partial Least Square-Structural Equation Model regression technique. Result: Results of the study shows that firm tenure and size have positive and significant relationship with auditor independence. Control variable, provision of non-audit assurance services also has positive and significance relationship with independence. However, the second control variable, audit fees, showed a positive but insignificant relationship with auditor independence. Conclusion: Based on these findings, the study concludes that audit firm tenure, rendering of non-assurance audit services impairs independence while audit firm size enhances it. Unique Contribution: The study provides further evidence through a more robust analytical procedure (PLS-SEM regression technique) that audit firm attributes of tenure and rendering of non-audit assurances services impair independence while size enhances it in Nigeria’s listed manufacturing companies. Key Recommendations: The study therefore recommends that regulatory provision of rotation of auditors be respected; there should be lifting of the veil of incorporation to ascertain companies that provide non audit services and sanction of auditors if it is discovered that they are providing non-audit services to their audit client under another name. It should also be ensured that accountants that are licensed to practice come together and practice as partners in a partnership instead of practicing as sole practitioners.